A Agenda 2030 e as tecnologias no enriquecimento do processo de alfabetização de crianças em situação de vulnerabilidade - Pegoraro, Aline Silveira Machado (2022)
This study, linked to the research line Management of Educational Technologies in Network, of the Graduate Program in Educational Technologies in Network and of the Interdisciplinary Research Group in Education, of the Federal University of Santa Maria, covered the theme of Agenda 2030 and the technologies to enrich the literacy process of children in vulnerable situations. In turn, the main objective was to identify the technological alternatives existing in the school that could enrich the literacy process of children in situations of social vulnerability, following the research problem: how technology contributes to the literacy of children in situation of social vulnerability? As for the theoretical foundation, it was guided through the path of construction of the 2030 agenda, the bibliographic research using the history of literacy with a timeline of programs and public policies, as well as theoretical support from authors referring to the theme, such as Freire ( 1983), Ferreiro (1996, 1999), among others. For this, the methodological procedures followed corroborate with a research with a qualitative descriptive approach of the participant type, using as an instrument for the collection and production of the data a semi-structured interview applied to the teachers of the first and second years of the initial years of elementary school and to the manager from a public teaching institution of the municipal network, located in the peripheral zone of the city of Santa Maria, RS, for the analysis of the data, the discourse analysis and categorical analysis of Bardin (2011) were used, in which five categories emerged: literacy, international policies, social vulnerability, technologies, active methodologies. Through the categories, it was possible to obtain the results in which the teachers understand literacy as a process that depends on previous experiences at school; they do not have knowledge about international policies and do not seek to know; the community around the school is highly vulnerable; technologies combined with active methodologies provide a more attractive and autonomous education for children.